A consonância entre educação, cultura e patrimônio: um estudo das ações educacionais e pedagógicas da Escola de Artes e Ofícios Thomaz Pompeu Sobrinho. - Oliveira, Dayana Silva de (2019)
This thesis aims to study the historical process of creation and development, the pedagogical and educational work of the School of Arts and Trades Thomaz Pompeu Sobrinho - EAOTPS, located in the neighborhood of Jacarecanga in the city of Fortaleza, Ceará. It is also proposed to verify the impacts of its educational proposal in the field of heritage education in the alumni, through their own narratives. We will see here a reflexive study on educational formation, based on its courses offered to the community strengthen; the results that awaken in students from reports of their appropriations and their memories. Researching educational institutions such as EAOTPS contributes to the identification, appropriation, conservation and preservation of the cultural heritage of Ceará. This is a qualitative research in the field of the history of education, where it was chosen to make a study with texts, analysis and interpretations. Among the methodological procedures used are field research, bibliographical research and documentary research. The narratives of the subjects participating in the School (employees, former employees and former students) were a significant source of data for this study. The work brings in its results the study and reflection on the history and memory of an educational institution and the pedagogical actions that contribute to the preservation and appreciation of the cultural heritage of Ceará.